2021
DOI: 10.1128/msphere.00699-21
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Vesicles Displaying a Heterologous PcrV-HitA Fusion Antigen Promote Protection against Pulmonary Pseudomonas aeruginosa Infection

Abstract: Hospital- and community-acquired infections with Pseudomonas aeruginosa cause a high rate of morbidity and mortality in patients who have underlying medical conditions. The spread of multidrug-resistant P. aeruginosa strains is becoming a great challenge for treatment using antibiotics. Thus, a vaccine as one of the alternative strategies is urgently required to prevent P. aeruginosa infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Cytokines from the BALF of mice on day 2 post-secondary bacterial challenge were measured by the Bio-Plex Pro Mouse Cytokine 23-Plex kit (Bio-Rad) as per the manufacturer ’ s protocol. The OPK assay was performed as previously described 28 and described in detail in the SI Materials and Methods .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines from the BALF of mice on day 2 post-secondary bacterial challenge were measured by the Bio-Plex Pro Mouse Cytokine 23-Plex kit (Bio-Rad) as per the manufacturer ’ s protocol. The OPK assay was performed as previously described 28 and described in detail in the SI Materials and Methods .…”
Section: Methodsmentioning
confidence: 99%
“…To enhance the efficacy of protein vaccines and promote mucosal immune responses, there is emergent interest in the application of bacterial vesicles or other nanoparticles delivering candidate pneumococcal proteins as vaccines 24 26 . Recently, we have established a self-adjuvanting Yersinia pseudotuberculosis (Yptb) outer membrane vesicle (OMV) platform to deliver heterologous antigens to achieve protection against corresponding respiratory bacterial infections 27 , 28 . In this proof-of-concept study, we employed the improved Yptb OMV platform 29 to deliver the highly immunogenic α-helical region of PspA (designated as OMV-PspA).…”
Section: Introductionmentioning
confidence: 99%
“…This is the rst time that proved γδ 17 T immune response induced by vaccine play an important role to resistant to P. aeruginosa pneumonia. An important role for IFN-γ and IL-17A in protection against P. aeruginosa infection after intramuscular vaccination with PcrV-HitAT (PH) fusion antigen has been previously reported 59 . Here, we demonstrated that protection from P. aeruginosa pneumonia elicited by P. aeruginosa antigen and EPS301 was fully dependent on IL-17A.…”
Section: Discussionmentioning
confidence: 97%
“…They consist of a portion of the outer membrane and other protein components which elicit a strong inflammatory response in host tissues [ 107 ]. Delivery of vaccine antigens via OMVs has been shown to stimulate potent humoral and Th1/Th17 responses in vivo [ 108 , 109 ], more so than isolated administration of vaccine antigens. The licensed Bexsero Meningococcal Group B vaccine uses OMV technology [ 110 ]; however, it has yet to be tested as a platform for P. aeruginosa antigen delivery.…”
Section: New Developments In P Aeruginosa Vaccinologymentioning
confidence: 99%